Time to treatment initiation: An analysis of sarcoma patients treated at Multidisciplinary-Team/Sarcoma-Board (MDT/SB's) over a four-year period. (1st June 2022) - Schärer, M; Heesen, P; Theus-Steinemann, C; Bode, B; Fuchs, B
Abstract: Objective: It is hypothesized that in the treatment of patients with soft tissue sarcomas (STS) the interval from establishing the diagnosis until initiation of treatment is relevant for the overall survival. Therefore, time to treatment initiation (TTI) was defined as a quality indicator for monitoring the treatment standard. The primary objective of this study was to find out how long (in days) it takes from establishing the sarcoma diagnosis through biopsy until initiation of treatment in patients suffering from STS. Secondary objectives were defined as the comparison between the different dignities, the different institutions and how the Swiss Sarcoma Network (SSN) cohort compares to the international standard. Methods: This is a retrospective analysis of prospectively collected data from the SSN. All patients being presented to the MDT/SB within a four-year period from 2018 to 2022 were included in this study. TTI and secondary objectives were determined using non-parametric summary statistics and presented as median and interquartile range. Ethic approval was granted for this study. Results: In total 383 patients were recorded in the respective time period in the SSN. In this study 278 patients with a malignant or intermediate STS according to WHO2020 were included. There were 66% (n=185) with a malignant and 44% (n=93) with an intermediate STS. The median TTI was 23 (8‐52) days. In the malignant group, the median TTI was 21 (5‐43) days and in the intermediate group 32 (11‐59) days. In the different institutions the median TTI's were 10 (-6‐30), 28 (12‐78), 24 (10‐58), 24 (10‐53) and 12 (-12‐54) days. Conclusion: In the SSN cohort the overall median TTI was 23 days. In the literature, a TTI delay of more than 42 days led to a slightly reduced overall survival. Compared to the international standard, we conclude that within the SSN network, patients face an adequate waiting time until treatment initiation with no potential restrictions to overall survival.